Pengaruh Konservatisme Akuntansi Dan Penghindaran Pajak Terhadap Nilai Perusahaan - Juli Ismanto; Puradinda Zulfiara (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
Aim of this research is to determine the effect of accounting conservatism and tax avoidance on firm value. The type of data used in this study is secondary data in the form of annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2013-2016 period. The number of samples is 48 manufacturing companies. The data analysis technique used is regression analysis. The results of the study show that conservatism has a positive effect on firm value, tax avoidance has a negative effect on firm value. While simultaneously conservatism and tax avoidance have a positive effect on firm value. Thus this study supports that accounting conservatism has a role as a function of monitoring the company's investment policies and one way to maintain the value of the company in limiting losses that may arise from poorly performing investment decisions. The company that conducts tax avoidance (has a smaller effective tax rate) is an effort made by management to reduce the company's tax burden and is able to minimize expenditure for tax purposes so that management looks good in the eyes of shareholders